Clinical and molecular characterization by next generation sequencing of Spanish patients affected by congenital deficiencies of fibrinogen. Issue 180 (August 2019) - Moret, Andrés; Zúñiga, Ángel; Ibáñez, Mariam; Cid, Ana Rosa; Haya, Saturnino; Ferrando, Fernando; Blanquer, Amando; Cervera, José; Bonanad, Santiago
Highlights: Fibrinogen quantity or quality deficiency can lead both to bleeding and thrombotic phenotype. Fibrinogen FGA, FGB and FGG genes were sequenced in 17 patients by next-generation sequencing. Variants leading to fibrinogen deficiency were found in all patients. Eight novel variants were described.